UJI EFEKTIVITAS JAMUR Metarhizium anisopliae Cps.T.B ISOLAT LOKAL TERHADAP RAYAP (Coptotermes curvignathus) - Rozalia '; Atria Martina; Titrawani ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Termite is one of the major pest on oil palm plantations, especially in peat soil. Application of synthetic insecticides will cause resistant insect, enviromental pollution, and other problems. The entomopathogenic fungus Metarhizium anisopliae has been reported to infect many insects, including termite. This study was aimed to analyze the effectiveness of treatment of M. anisopliae Cps.T.B and M. anisopliae Cps.T.B with zeolit in controlling termite, C. curvignathus. This research used a completely randomized design with three treatments and eight replications. The result showed that spore density of M. anisopliae Cps.T.B with zeolite was 2,5 x108 spores/g and M. anisopliae Cps.T.B without zeolite was 3,2 x108 spores/gram respectively. Germination ability of M. anisopliae Cps.T.B with zeolite was 91.11% and M. anisopliae Cps.T.B without zeolite was 87.41% respectively. Mortality of C. curvignathus on eight days after treatment using M. anisopliae Cps.T.B was 100% and using M. anisopliae Cps.T.B with zeolite was 95,5% while the mortality of C. curvignathus a control was 15%.